Applying a social equity approach to transformative climate change adaptation - Hellin, Jon; Ringler, Claudia; Menon, Purnima (CGIAR, 2023)
A social equity approach to operationalize transformative methodologies helps minimize maladaptation including adverse impacts on women and indigenous peoples. In terms of climate risk, social equity relates to responsibility for and distribution of climate impacts and policies across society, generations and genders, including in terms of who participates in and controls decision-making. Attention to social equity enables those conducting research to consider how social difference and associated inequalities shape vulnerability and influence people’s access to innovations to build resilience and improve their livelihoods. A neglected topic is how to enhance scientific support for indigenous peoples’ knowledge and practices in the pursuit of climate resilient agriculture. This event will feature work in Kenya by the Centre for Minority Rights and Development (CEMIRIDE) and the CGIAR Initiative on Climate Resilience, whereby community members share their own solutions for equitable climate change adaptation. More broadly, the event also identifies complimentary approaches such as social protection that in circumstances may be required to enhance marginalized groups’ (women and indigenous peoples) access to resources, services, institutions and economic opportunities.